Stressing Reproduction: Reading Into Parents of Disabled Children - Gibson, Margaret F. (Disability Studies Quarterly, 2012)
What does is mean to be the parent of a disabled child? This article explores assumptions which permeate the author's encounter with of a prominent Canadian newspaper text on "stress". Through a hermeneutic phenomenological method, the author opens up broader cultural meanings that contribute to and rely upon the category of "parents of disabled children". In particular, the author explores the prescriptions presented on disability, race, class, gender, nationality, and sexuality which emerge in the reading process. Additionally, the author considers how medico-scientific authority is asserted in this textual encounter, and examines the historical grounding of such interpretive moves. Keywords stress, parents, mothers, fathers, history, disability, gender, nation, race, class, sexuality, reproduction, children